2015
DOI: 10.1109/jphotov.2014.2360566
|View full text |Cite
|
Sign up to set email alerts
|

Limiting Light Escape Angle in Silicon Photovoltaics: Ideal and Realistic Cells

Abstract: Restricting the light escape angle within a solar cell significantly enhances light trapping, resulting in potentially higher efficiency in thinner cells. Using an improved detailed balance model for silicon and neglecting diffuse light, we calculate an efficiency gain of 3% ab s for an ideal Si cell of 3-μm thickness and the escape angle restricted to 2.767°under AM1.5 direct illumination. Applying the model to current high-efficiency cell technologies, we find that a heterojunction-type device with better su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Moreover, because of the optical recycling, thinner solar cells can be used which benefit from lower Auger and (bulk) Shockley-Read-Hall charge-carrier recombination, which results in a higher open circuit voltage (V oc ). Thereby, the theoretical efficiency limit of this type of angular restriction is significantly higher than that of cells without angular restriction [1,6].…”
Section: Introduction To the Light Trapping Modulementioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, because of the optical recycling, thinner solar cells can be used which benefit from lower Auger and (bulk) Shockley-Read-Hall charge-carrier recombination, which results in a higher open circuit voltage (V oc ). Thereby, the theoretical efficiency limit of this type of angular restriction is significantly higher than that of cells without angular restriction [1,6].…”
Section: Introduction To the Light Trapping Modulementioning
confidence: 89%
“…There has been significant interest in angular confinement for solar energy by many authors using rugate filters, interference filters, and light confining cavities to address the aforementioned issues [1][2][3][4][5][6][7][8]. State-of-the-art rugate filters and interference filters enable wavelength and angular selective transmission (and reflection) based on interference due to Fresnel reflection in their refractive index profile.…”
Section: Introduction To the Light Trapping Modulementioning
confidence: 99%
“…Alternative LM strategies include luminescent solar concentrators that absorb and selectively re-emit light in the active layer, 178 or nanostructures able to restrict the light emission angle to potentially reduce entropy losses due to light emission. 28,179 Computational methods available to study LM at the nm-mm scale focus on computing the electromagnetic field within the active layer by solving Maxwell's equations. Among different possible implementations, a popular choice is finite-difference time-domain (FDTD) simulations propagating Maxwell's equation in time using real-space grids.…”
Section: Sunlight Management Across Length Scalesmentioning
confidence: 99%
“…For solar cells with diffusive back reflector (Fig. 9A) [75], it has been theoretically shown that limiting the emission angle in the solar spectrum can reduce the optical escape cone and enhance the light trapping [31,65,76,77]. Enhanced light trapping effect allows for better absorption of sunlight in a very thin cell (reducing material usage), and an increase in current, voltage and efficiency of the solar cell as well.…”
Section: Solar Cellsmentioning
confidence: 99%